2011
DOI: 10.1177/1090820x10395010
|View full text |Cite
|
Sign up to set email alerts
|

An In Vivo Comparison of Barbed Suture Devices and Conventional Monofilament Sutures for Cosmetic Skin Closure Biomechanical Wound Strength and Histology

Abstract: Knotless, absorbable barbed suture devices are a safe and efficacious alternative for cosmetic skin closures and yield wound strength and tissue reaction scores that are comparable to those from closures performed with absorbable monofilament sutures and secured with knots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
120
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(138 citation statements)
references
References 8 publications
10
120
3
1
Order By: Relevance
“…Previous studies showed there were less infections in contaminated wounds closed with monofilament suture compared with braided suture [1,10,20]. Several studies have shown bacteria adhere more tightly to braided suture [2,10,12,13,25,27] and that braided suture leads to more infections as compared with monofilament suture [1,9,10,14,28].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed there were less infections in contaminated wounds closed with monofilament suture compared with braided suture [1,10,20]. Several studies have shown bacteria adhere more tightly to braided suture [2,10,12,13,25,27] and that braided suture leads to more infections as compared with monofilament suture [1,9,10,14,28].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the needle size, the bi-directional knotless suture still had complications, such as the increased secondary tissue damage, similar to Woodley et al [34]. However, the bi-directional knotless suture proved to be a superior method, opposed to interrupted sutures, for many internal and external surgical techniques in humans as it reduces surgical time and increases the rate of healing [27,33], while maintaining wound strength similar to that of monofilament sutures [32].…”
Section: Discussionmentioning
confidence: 86%
“…In addition, irritation has been related to tissue trauma by the number of entry/ exit suture points and knot sizes [24,39]. In humans, tissue reactions were found to be similar between barbed suture wound closures and monofilament wound closures [32], similar results were found with the use of the barbed sutures in juvenile Chinook salmon [34]. Comparable to juvenile Chinook salmon held at 12°C [34], the juvenile Chinook salmon, in this study, with the 6-Point pattern exhibited the greatest amount of ulceration and erythema followed by fish whose incisions were closed with the knot patterns, and lastly the pattern with the least suture material exposed to the fish, the Wide "N" pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiotech Pharmaceuticals Inc., with the development of the Quill™ suture retention system for wound closure. In 2007, absorbable barbed sutures became available for commercial use and these have been used in all surgical specialties for soft tissue fixation over the past decade [2]. Covidien™ and Ethicon™ have both developed their own barbed suture technologies.…”
Section: Introductionmentioning
confidence: 99%